2021
DOI: 10.1001/jamaophthalmol.2021.0320
|View full text |Cite
|
Sign up to set email alerts
|

Association of Retinal Changes With Alzheimer Disease Neuroimaging Biomarkers in Cognitively Normal Individuals

Abstract: IMPORTANCERetinal biomarkers reflecting in vivo brain Alzheimer disease (AD) pathologic abnormalities could be a useful tool for screening cognitively normal (CN) individuals at the preclinical stage of AD.OBJECTIVES To investigate the association of both functional and structural alterations of the retina with in vivo AD pathologic abnormalities in CN older adults and model a screening tool for detection of preclinical AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
1
30
1
Order By: Relevance
“…As a preclinical marker, however, no association was found between GC-IPL thickness and increased risk of incident dementia [hazard ratio (HR) 1.13, confidence interval (CI): 0.9–1.43] in the Rotterdam study (in contrast to RNFL thickness as previously discussed) 18 . Nonetheless, GC-IPL thinning has been associated with the prevalence of MCI in a meta-analysis, 21 has been shown to be more sensitive than RNFL thickness in detecting MCI in patients with positive in vivo biomarkers for AD, 36 and has recently been associated with cognitively normal patients with AD-related neurodegeneration 30 . One possible explanation for the discrepancy between the positive structural and negative functional findings is the temporal lag between the onset of dementia and the manifestation of GC-IPL thinning.…”
Section: Evidence For Retinal Biomarkersmentioning
confidence: 89%
See 2 more Smart Citations
“…As a preclinical marker, however, no association was found between GC-IPL thickness and increased risk of incident dementia [hazard ratio (HR) 1.13, confidence interval (CI): 0.9–1.43] in the Rotterdam study (in contrast to RNFL thickness as previously discussed) 18 . Nonetheless, GC-IPL thinning has been associated with the prevalence of MCI in a meta-analysis, 21 has been shown to be more sensitive than RNFL thickness in detecting MCI in patients with positive in vivo biomarkers for AD, 36 and has recently been associated with cognitively normal patients with AD-related neurodegeneration 30 . One possible explanation for the discrepancy between the positive structural and negative functional findings is the temporal lag between the onset of dementia and the manifestation of GC-IPL thinning.…”
Section: Evidence For Retinal Biomarkersmentioning
confidence: 89%
“…Total macular thickness measurements have similarly been reported to be decreased in patients with MCI, AD, 20 and preclinical disease with positive in vivo biomarkers 30 . However, some studies have demonstrated only weak correlations between macular thickness in AD versus control populations, and predominantly in specific regions of the macula.…”
Section: Evidence For Retinal Biomarkersmentioning
confidence: 98%
See 1 more Smart Citation
“…Cell bodies of RGCs comprise the retinal nerve fiber layer (RNFL), and axons of RGCs form the optic nerve. This is where synaptic connections via the dorsal lateral geniculate nucleus terminate in the visual cortex [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its particular structure and the ease of access to the eye make this organ a candidate for obtaining potentially useful parameters in this sense, bearing in mind its involvement in a multitude of systemic processes whose rst sign may even show itself as an ophthalmological symptom 12 . Recently, ophthalmologic ndings have been associated with preclinical neurologic conditions as Alzheimer's disease 13,14 . Moreover, changes in the cardiovascular system have also been related with signs that are visible in the eye, making this organ a window that provides quick access to the cardiovascular system thanks to the ease with which it is possible to see ndings 15 .…”
Section: Introductionmentioning
confidence: 99%